Sensitivity and Treatment of Infectious Mastitis Pathogens in Cows to Antibiotics - Ikromovich, Amirov Abdumumin; Abdurasul og‘li, Abdurasulov Shavkat; Abdusalom, Abdusattorov; Bakhrom qizi, Norbutaeva Sabrina (American Journal of Biology and Natural Sciences, 2026)
The article presents data on the sensitivity of pathogens (staphylococci, streptococci, enterococci, Escherichia, Proteus, and Pseudomonas) to antibacterial drugs prior to the treatment of cows suffering from infectious mastitis. The sensitivity of these microorganisms to penicillin, streptomycin, sulfadiazine, chloramphenicol, tetracycline, enrofloxacin, kanamycin, monomycin, polymyxin, erythromycin, oleandomycin, tylosin, as well as anti-mastitis preparations Mastisan and Mastisept, was determined by the indicator disk method. When the diameter of the growth inhibition zone of the culture was 15–25 mm, sensitivity was evaluated as moderate; more than 25 mm as high; and the absence of an inhibition zone indicated resistance of the microorganism to the corresponding antibiotic. The results of sensitivity studies of the above-mentioned staphylococci, streptococci, enterococci, Escherichia, Proteus, and Pseudomonas to antibacterial drugs are presented. It was established that the average overall effectiveness of treatment of serous, catarrhal, fibrinous, purulent, and subclinical mastitis with Mastisan was about 80%. The Mastisept preparation showed an average overall treatment effectiveness of 85% for the indicated forms of mastitis, while in 14% of cows incomplete recovery of milk productivity was observed.